A fish supper and a chippy smile. love, hardship and laughter in a South East London fish-and-chip shop /: love, hardship and laughter in a South East London fish-and-chip shop. Chapters 6-11 : Part two, (2015) - Kemp, Hilda; Kemp, Cathryn
No abstract available